2018
DOI: 10.1002/2211-5463.12508
|View full text |Cite
|
Sign up to set email alerts
|

Corrigendum to: Contribution of histone N‐terminal tails to the structure and stability of nucleosomes

Abstract: Recently, Iwasaki et al. [1] noticed that the tlH4 (tail-less H4) protein used in their study contained an additional amino acid sequence, MVDLQAAANSLVIHM, at its N-terminal end. This sequence, which is derived from the cloning vector, was mistakenly inserted. Specifically, the tlH4 protein contains this additional sequence downstream of the N-terminal thrombin cleavage site and before the H4K16 residue, as shown below. GSH-MVDLQAAANSLVIHM-KRHRKVLRDNIQGITKPAIRRLARRGGVKRISGLIYEETRGVLKVFLE NVIRDAVTYTEHAKRKTVTAMD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
(1 reference statement)
0
1
0
Order By: Relevance
“…A density map obtained with classical subtomogram averaging (without taking into account conformational heterogeneity) was used as the reference density map for HEMNMA-3D ( Figure 10C ). The resolution of this reference density map is around 2 nm (as determined by Fourier Shell Correlation between the reference density map and the density map from the atomic nucleosome structure PDB:3w98 Iwasaki et al, 2013 shown in Figure 10B ). For more information on how this reference density map (global initial subtomogram average) was obtained, please see section 1 of the Supplementary Material (Nucleosome data preparation and acquisition).…”
Section: Resultsmentioning
confidence: 99%
“…A density map obtained with classical subtomogram averaging (without taking into account conformational heterogeneity) was used as the reference density map for HEMNMA-3D ( Figure 10C ). The resolution of this reference density map is around 2 nm (as determined by Fourier Shell Correlation between the reference density map and the density map from the atomic nucleosome structure PDB:3w98 Iwasaki et al, 2013 shown in Figure 10B ). For more information on how this reference density map (global initial subtomogram average) was obtained, please see section 1 of the Supplementary Material (Nucleosome data preparation and acquisition).…”
Section: Resultsmentioning
confidence: 99%